Microarray analysis of gene/transcript expression in Prader-Willi syndrome: deletion versus UPD. Issue 8 (14th August 2003) - Bittel, D C; Kibiryeva, N; Talebizadeh, Z; Butler, M G
Abstract : Background : Prader-Willi syndrome (PWS), the most common genetic cause of marked obesity, is caused by genomic imprinting and loss of expression of paternal genes in the 15q11–q13 region. There is a paucity of data examining simultaneous gene expression in this syndrome. Methods : We generated cDNA microarrays representing 73 non-redundant genes/transcripts from the 15q11–q13 region, the majority within the PWS critical region and others distally on chromosome 15. We used our custom microarrays to compare gene expression from actively growing lymphoblastoid cell lines established from nine young adult males (six with PWS (three with deletion and three with UPD) and three controls). Results : There was no evidence of expression of genes previously identified as paternally expressed in the PWS cell lines with either deletion or UPD. We detected no difference in expression of genes with known biallelic expression located outside the 15q11–q13 region in all cell lines studied. There was no difference in expression levels of biallelically expressed genes (for example, OCA2 ) from within 15q11–q13 when comparing UPD cell lines with controls. However, two genes previously identified as maternally expressed ( UBE3A and ATP10C ) showed a significant increase in expression in UPD cell lines compared with control and PWS deletion subjects. Several genes/transcripts (for example, GABRA5, GABRB3 ) had increased expression in UPD cell lines compared with deletion, but less than controls indicating paternal bias. Conclusions : Our results suggest that differences in expression of candidate genes may contribute to phenotypic differences between PWS subjects with deletion or UPD and warrant further investigations.